FACTORS AFFECTING THE QUALITY OF LIFE OF PATIENTS’ USING HEMODIALYSIS AT TGK CHIK DITIRO HOSPITAL, SIGLI - Siddiq, T M; Aletta, Alma; Arifin, Vera Nazhira; Wardiati, Wardiati; Septiani, Riza (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Chronic Kidney Disease (CKD) is a condition of progressive and permanent decline of kidney function resulting in various diseases. CKD patients may be at risk of their lives if they do not undergo periodic hemodialysis or kidney transplantation to replace severely damaged kidneys. The aim of this study is to analyze the Factors Influencing the Quality of Life of Patients Using Hemodialysis Therapy at Tgk Chik Ditiro Sigli Hospital in 2020. Method: This research is descriptive with a cross-sectional approach using a questionnaire as the data collection instrument. The study population consists of all patients undergoing Hemodialysis at Tgk Chik Ditiro Sigli Hospital in 2020. The sample consisted of 60 patients using total sampling technique. Data collection was conducted in November 2020. The quality of life assessment questionnaire used was the WHOQOL-BREF. Results: There is a relationship between self-efficacy (p value 0.040), motivation (p value 0.001), family support (p value 0.006), anxiety (p value 0.000) and the quality of life of hemodialysis patients. Recommendations: Pidie District Government may facilitate improvement of self-efficacy. self-motivation. and reduce the level of anxiety among patients. The Pidie District Health Office may implement socialization regarding kidney disease prevention efforts. Tgk Chik Ditiro Sigli Hospital may to provide excellent care in improving the quality of life of patients using hemodialysis therapy.